Analisis Perbandingan Kinerja Protokol AOMDV, DSDV, Dan ZRP Sebagai Protokol Routing Pada Mobile Ad-Hoc Network (MANET) - Fatkhurrozi Fatkhurrozi; Edita Rosana Widasari; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Natural disaster is an event that can cause damage to communication network's infrastructure in a region. Therefore, a network technology that is able to run independently without the infrastructure of communication and internet networks; such as BTS, router, or access point, is required. The technology is called Mobile Ad-Hoc Network (MANET). MANET is a wireless network consisting of a set of mobile nodes that communicate in a multi-hop manner inside a dynamic topology without depending on a supporting infrastructure. MANET routing protocols are generally classified into three types, such as reactive, proactive, and hybrid routing protocols. These three types of routing protocols have different algorithms in route search methods. Among the three types of routing protocols, there are AOMDV, DSDV, and ZRP. This research was propsed to compare the performance of three different types of routing protocols, such as AOMDV, DSDV, and ZRP when simulated in different scopes. Simulations were performed using Network Simulator 2 and measured by four parameters such as throughput, end-to-end delay, packet delivery ratio, and normalized routing load. Based on the tests that were conducted in different range area and number of mobile nodes scenarios, it can be concluded that AOMDV has the highest average packet delivery ratio and throughput value. On the other hand, it was found that the best average value was obtained by DSDV protocol during the measurement of end-to-end delay and normalized routing load.